Gobi : a little dog with a big heart - Leonard, Dion; Wiley, Lisa (Manuzak Wiley) (Nashville: Tommy Nelson publishers, 2017)
"Bring home the incredible true story of a friendship so strong that it crosses the globe! Families everywhere will be delighted by the tale of Gobi, a little dog living all alone in China's Gobi Desert, and Dion Leonard, a successful ultramarathon runner."--
Color Illustrations
Children
Keywords: Gobi -- (Dog) -- Juvenile literature; Leonard, Dion -- Juvenile literature; Gobi -- (Dog).; Leonard, Dion; Dogs -- Gobi Desert (Mongolia and China) -- Biography; Male long-distance runners -- Biography; Human-animal relationships -- Juvenile literature; Dogs -- Gobi Desert (Mongolia and China).; Male long-distance runners; Human-animal relationships; Human-animal relationships; Biographies